Treatment outcomes of alginate-embedded allogenic mesenchymal stem cells versus autologous chondrocytes for the repair of focal articular cartilage defects in a rabbit model - Tay, L.X.; Ahmad, R.E.; Dashtdar, H.; Tay, K.W.; Masjuddin, T.; Ab-Rahim, S.; Chong, P.P.; Selvaratnam, L.; Kamarul, Tunku (SAGE Publications (UK and US), 2011)
Background: Mesenchymal stem cells (MSCs) represent a promising alternative form of cell-based therapy for cartilage injury. However, the capacity of MSCs for chondrogenesis has not been fully explored. In particular, there is presently a lack of studies comparing the effectiveness of MSCs to conventional autologous chondrocyte (autoC) treatment for regeneration of full-thickness cartilage defects in vivo. Hypothesis: Treatment with allogenic undifferentiated MSCs (alloMSCs) results in superior cartilage tissue regeneration profiles when compared with autoC for repair of focal articular cartilage defects. Study Design: Controlled laboratory study. Methods: Full-thickness articular cartilage defects were created on the weightbearing surface of the medial femoral condyles in both knees of New Zealand White rabbits (N = 30). Six weeks after the defect was induced, the right knee was treated with either alloMSCs (n = 12) or autoC (n = 18), while the left knee remained untreated (control). The rabbits were sacrificed at 6 months after treatment for assessment of cartilage tissue regeneration, which included the Brittberg morphologic score, histologic grading by O'Driscoll score, and quantitative analysis of glycosaminoglycans per total protein content. Results: Apart from significantly higher Brittberg scores in the alloMSC treatment group (8.8 +/- 0.8) versus the autoC treatment group (6.6 +/- 0.8) (P = .04), both treatments showed similar cartilage regenerative profiles. All outcome measures were significantly higher in the treatment groups compared with their respective controls (P < .05). Conclusion: AlloMSCs have similar effectiveness as autoC for repair of focal cartilage defects. Both treatments resulted in superior tissue regeneration compared with untreated defects. Clinical Relevance: The results have an implication of supporting the potential use of MSCs for cartilage repair after sports injuries or diseases, in view of similar efficacy but less patient morbidity and potential cost savings as compared with conventional autoC therapy.